2022
DOI: 10.1002/acr.24968
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Quantity, Duration, and Type of Alcohol Consumption on the Development of Gouty Tophi

Abstract: Objective To examine the association of alcohol consumption with the presence and development of ultrasound (US)–detected tophi and subcutaneous tophi in a Chinese gout population. Methods A total of 554 patients with gout who underwent US and physical examination of the most frequently involved joints in gout were included in this study. Multivariable analysis was performed to assess the associations of the duration, quantity, and type of alcohol consumption with the presence, size, and number of US‐detected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
1
1
0
Order By: Relevance
“…Alcohol consumption was recently linked to tophi 33 and to a poor sUA outcome 22 in gout, and had also observed by us after 1 -year, 24 but alcohol consumption did not predict the 2-year sUA outcome. A familial interaction between obesity and alcohol consumption has been found to contribute to gout.…”
Section: Discussionsupporting
confidence: 60%
“…Alcohol consumption was recently linked to tophi 33 and to a poor sUA outcome 22 in gout, and had also observed by us after 1 -year, 24 but alcohol consumption did not predict the 2-year sUA outcome. A familial interaction between obesity and alcohol consumption has been found to contribute to gout.…”
Section: Discussionsupporting
confidence: 60%
“…Recent analysis by Lin Han et al To determine that chronic and excessive alcohol consumption is a key predictor of tophi and subcutaneous tophi manifestations in patients with gout. In addition, their report linked weekly alcohol consumption to tophi progression in individuals who already had speculative tophi ( 54 ). These findings were corroborated by a study conducted by Tuhina Neogi et al, which demonstrated that the risk of gout recurrence was elevated irrespective of the type of alcoholic beverage consumed, and was linked to occasional alcohol intake ( 55 ).…”
Section: Discussionmentioning
confidence: 99%